derivada da função raiz de 3x¹-7
Soluções para a tarefa
Respondido por
0
Regra da cadeia:
![\boxed{\boxed{\dfrac{d}{dx}f(g(x))=f'(g(x))\cdot g'(x)=\dfrac{dy}{du}\dfrac{du}{dx}}} \boxed{\boxed{\dfrac{d}{dx}f(g(x))=f'(g(x))\cdot g'(x)=\dfrac{dy}{du}\dfrac{du}{dx}}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cboxed%7B%5Cdfrac%7Bd%7D%7Bdx%7Df%28g%28x%29%29%3Df%27%28g%28x%29%29%5Ccdot+g%27%28x%29%3D%5Cdfrac%7Bdy%7D%7Bdu%7D%5Cdfrac%7Bdu%7D%7Bdx%7D%7D%7D)
______________________
![f(x)=\sqrt{3x-7} f(x)=\sqrt{3x-7}](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%7B3x-7%7D)
Seja
e ![g(x)=3x-7 g(x)=3x-7](https://tex.z-dn.net/?f=g%28x%29%3D3x-7)
Então
![h(g(x))=\sqrt{g(x)}=\sqrt{3x-7}~~~~\therefore~~~~\boxed{\boxed{f(x)=h(g(x))}} h(g(x))=\sqrt{g(x)}=\sqrt{3x-7}~~~~\therefore~~~~\boxed{\boxed{f(x)=h(g(x))}}](https://tex.z-dn.net/?f=h%28g%28x%29%29%3D%5Csqrt%7Bg%28x%29%7D%3D%5Csqrt%7B3x-7%7D%7E%7E%7E%7E%5Ctherefore%7E%7E%7E%7E%5Cboxed%7B%5Cboxed%7Bf%28x%29%3Dh%28g%28x%29%29%7D%7D)
Portanto:
![f'(x)=h'(g(x))\cdot g'(x)\\\\\\f'(x)=\dfrac{1}{2\sqrt{3x-7}}\cdot\dfrac{d}{dx}(3x-7)\\\\\\f'(x)=\dfrac{1}{2\sqrt{3x-7}}\cdot3\\\\\\\boxed{\boxed{f'(x)=\dfrac{3}{2\sqrt{3x-7}}}} f'(x)=h'(g(x))\cdot g'(x)\\\\\\f'(x)=\dfrac{1}{2\sqrt{3x-7}}\cdot\dfrac{d}{dx}(3x-7)\\\\\\f'(x)=\dfrac{1}{2\sqrt{3x-7}}\cdot3\\\\\\\boxed{\boxed{f'(x)=\dfrac{3}{2\sqrt{3x-7}}}}](https://tex.z-dn.net/?f=f%27%28x%29%3Dh%27%28g%28x%29%29%5Ccdot+g%27%28x%29%5C%5C%5C%5C%5C%5Cf%27%28x%29%3D%5Cdfrac%7B1%7D%7B2%5Csqrt%7B3x-7%7D%7D%5Ccdot%5Cdfrac%7Bd%7D%7Bdx%7D%283x-7%29%5C%5C%5C%5C%5C%5Cf%27%28x%29%3D%5Cdfrac%7B1%7D%7B2%5Csqrt%7B3x-7%7D%7D%5Ccdot3%5C%5C%5C%5C%5C%5C%5Cboxed%7B%5Cboxed%7Bf%27%28x%29%3D%5Cdfrac%7B3%7D%7B2%5Csqrt%7B3x-7%7D%7D%7D%7D)
______________________
Seja
Então
Portanto:
Perguntas interessantes
Português,
1 ano atrás
História,
1 ano atrás
Inglês,
1 ano atrás
Sociologia,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás